Kreativitas Guru Paud Dalam Mengajar Calistung Pada Anak - Maryani, Sri; , Rini Lestari, S.Psi, M.Si (2017)
Early childhood education is to educate early-aged 0-6 years with able to developpotential. Its existence is an important factor in early childhood education are teachers. The goal in this research is to know the forms of creativity guru OLD Cluster Joy Sumberlawang Subdistrict in teaching 33 March 2011 on his protégé. This research is a descriptive analytical study was carried out in the OLD Cluster Joy Sumberlawang Subdistrict. The subject of this research is the teachers that teachin the OLD Cluster of joy that add up to 3 people. The object of the research was the teachers creativity in learning reading, writing, and counting. The data collection method used is the observation or observation and interview. Technique of data analysis in this research is qualitative. The results showed that 33 March 2011 study gives hope for both the teacher andstudents and parents of students. These forms of creativity of teachers in learning33 March 2011 is to play while learning or studying while playing. The child was not prosecuted but learning outcomes the process of learning that goes on. Teachers using the method of playing and using the media to be around schools or media that you have prepared as the media image of fruit and puzzle. Children are given the leeway to develop its own talent and his creativity to discover and understand the shape and symbol numbers nor letters found children through playing around the school. Keywords: 33 March 2011, teacher, OLD